Asymmetric hydrogenation of an α-unsaturated carboxylic acid catalyzed by intact chiral transition metal carbonyl clusters – diastereomeric control of enantioselectivity. Issue 14 (27th February 2020) - Abdel-Magied, Ahmed F.; Theibich, Yusuf; Singh, Amrendra K.; Rahaman, Ahibur; Doverbratt, Isa; Raha, Arun K.; Haukka, Matti; Richmond, Michael G.; Nordlander, Ebbe
Abstract : Asymmetric hydrogenation catalysis by [(μ-H)2 Ru3 (μ3 -S)(CO)7 (μ-P–P*)] (P–P* = chiral diphosphine) indicates intact chiral clusters as active catalysts. Abstract : Twenty clusters of the general formula [(μ-H)2 Ru3 (μ3 -S)(CO)7 (μ-P–P*)] (P–P* = chiral diphosphine of the ferrocene-based Walphos or Josiphos families) have been synthesised and characterised. The clusters have been tested as catalysts for asymmetric hydrogenation of tiglic acid [ trans -2-methyl-2-butenoic acid]. The observed enantioselectivities and conversion rates strongly support catalysis by intact Ru3 clusters. A catalytic mechanism involving an active Ru3 catalyst generated by CO loss from [(μ-H)2 Ru3 (μ3 -S)(CO)7 (μ-P–P*)] has been investigated by DFT calculations.